The influence of the noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP) resection diagnosis on the false‐positive thyroid cytology rate relates to quality assurance thresholds and the application of NIFTP criteria. Issue 9 (5th July 2017) - Ohori, N. Paul; Wolfe, Jenna; Carty, Sally E.; Yip, Linwah; LeBeau, Shane O.; Berg, Aaron N.; Schoedel, Karen E.; Nikiforov, Yuri E.; Seethala, Raja R.
Abstract : BACKGROUND: Noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP) is a newly defined entity and recent studies have suggested a decrease of a few percentage points in the rate of malignancy (ROM) for the positive‐for‐malignancy (PFM) cytology category as a result of NIFTP implementation. However, the distinction between a diagnosis of PFM and one of suspicious for malignancy (SFM) may depend on a variety of factors. In the current study, the authors investigated the ROM for the PFM and SFM diagnoses before and after histologic NIFTP reclassification. METHODS: Cytology cases with PFM and SFM diagnoses and subsequent surgical resection specimens were searched in the files of the study institution from September 2008 to September 2016. The surgical pathology cases of noninvasive encapsulated follicular variant of papillary thyroid carcinoma were reexamined to determine whether they qualified for NIFTP. The distinct ROMs for the PFM and SFM cases were calculated accordingly. RESULTS: The authors' search identified 338 cases of PFM and 139 cases of SFM with a resection outcome. Before NIFTP reclassification, the PFM cases had a ROM of 99.4%; after NIFTP reclassification, the ROM was 99.1% ( P = .6861). The ROM of the SFM cases decreased from 75.5% to 66.9% with NIFTP reclassification ( P = .1402). One case in the PFM group and 6 cases in the SFM group could not be verified due to insufficient sampling. CONCLUSIONS: In the current large series, NIFTP reclassification did not appear to significantly alter the high ROM for the PFM diagnosis. The authors attribute this finding to a strict quality assurance policy, an emphasis on key cytologic criteria, and systematic application of the NIFTP criteria to follicular‐patterned lesions. Cancer Cytopathol 2017;125:692‐700. © 2017 American Cancer Society . Abstract : Noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP) is a newly defined entity, and recent studies have suggested a decrease of a few percentage points in the rate of malignancy (ROM) for the positive‐for‐malignancy cytology category as a result of NIFTP implementation. The ROM for the cytology category of positive for malignancy does not appear to be affected significantly if the key criteria are applied rigorously to cytology cases and surgical specimens considered for the NIFTP reclassification.